Income analysis of hand line fishermen in Banawa Village, South Yapen District, Yapen Islands Regency, Papua Province - Lukman Daris; Akriani Dewi Bau Sinrang; Yuslam Alfred Ambokari; Jamaluddin (Sangia Research Media and Publishing, 2023)
The purpose of this study was to determine fishermen's income using hand line fishing gear in Banawa Village using primary data for 50 respondents representing the entire population of the Fisherman Community in Banawa Village. Data collection was carried out using interviews and documentation methods. The analytical method used is descriptive quantitative. The collected data is processed and presented in tabular form. The study results show that the fishing community in Kampung Banawa still needs a higher understanding of knowledge and technology. This has not reduced the enthusiasm of fishermen in Kampung Banawa to go to sea actively, even though the price of fish in the market could be better. There are differences between hand-line fishermen based on the boat used. Hand line fishermen with rowing boats earn Rp.70,000/week, hand line fishermen using ketinting engine boats Rp.120,000/week, and hand line fishermen using 15PK outboard motors make Rp.200,000/week. Institutions supporting fishermen's income include Fishery Cooperatives, Banking (BNI), and fish markets.